Water Stress Influence For Tomato (Solanum Lycopersicum) Production - Rusnam Rusnam; Ridho Adi Surya; Muhammad Makky (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2021)
Tomato, also known as Solanum lycopersicum, is one of the horticultural commodities that have a good priority to be developed. Tomato production in Indonesia has decreased over five decades. This lack of production is caused by the limitation of water supply during the dry season as to effect of its rooting. One of the ways of ensuring water supply is using an irrigation system, including drip irrigation. The use of drip irrigation will save a lot of water, but the allocation of water to be given will cause to salinity. This phenomenon requires actions to control the water for tomato production. Research in this area is being carried out in the subdistrict of Lubuk Kilangan, Padang City. The current study observes the effect of salinity on the amount of leaf, the productivity, and the sweetness of the tomato fruit. Based on the results, the efficiency of drip irrigation is around 96.28%, and there is no real effect of salinity on the amount of leaf. Additionally, salinity does not affect productivity. The highest productivity is on the treatment of giving water at -15%, amounting to 2.30 kg, and the lowest is at -5%, amounting to 1.72%. Salinity increases the sweetness of tomato, and the highest sweetness level is on the treatment of giving water at -20%, amounting to 5.6600 Brix, and the lowest sweetness level is at the control treatment, amounting to 5.1100 Brix.